OC-001 Endoscopic balloon dilatation for crohn's disease strictures: a systematic review and meta-analysis. (22nd June 2015) - Morar, P; Faiz, O; Warusavitarne, J; Brown, S; Cohen, R; Hind, D; Abercrombie, J; Ragunath, K; Sanders, DS; Arnott, I; Wilson, G; Bloom, S; et al.
Abstract : Introduction: Endoscopic balloon dilatation (EBD) is a recognised treatment for symptomatic Crohn's strictures. Several case studies report its short term and long term efficacy. A systematic analysis of the literature is needed to define overall efficacy and inform future study design. The primary objective was to examine symptomatic response, technical response and adverse events of EBD. The impact of stricture characteristics on outcome was also explored. Method: A systematic search was performed in accordance with PRISMA guidelines. The quality of individual studies was assessed using the Newcastle-Ottawa Scale. The results were expressed as a per patient analysis using the proportion of patients within a group and a per study analysis using pooled event rates across studies. The random effects model was expressed as forest plots and summative statistics. Heterogeneity across studies was assessed numerically (I 2 ). The mean value of pooled outcomes was used to create two groups (< or ≥ the pooled mean event rate [PMER]), to compare the effect of the proportion of patients within each group (e.g. stricture activity and type) on outcome. Results: Twenty-five studies were included: 1089 patients and 2664 dilatations. The grade for quality ranged from 2 to 6. The proportion of patients with symptomatic and technical response was 63.9% (393/615) and 92.6% (403/435) respectively. The proportion of patients with perforation was 2.6% (18/700). The PMER for symptomatic response was 74.8% (95% CI: 69.9–79.3%; I2: 0%), technical response was 90.6% (95% CI: 87.8–92.8%; I2: 11.7%), complications was 6.4% (95% CI: 5.0–8.2; I2: 4.0%), and perforation was 3% (95% CI: 2.2–4.0%; I2: 0%). The proportion of patients with active strictures demonstrating a < PMER and ≥ PMER for symptomatic response was 73% vs 60% respectively. The proportion of patients with active strictures demonstrating a ≥ PMER and < PMER for perforation was 62% and 36% respectively. The proportion of patients with anastomotic strictures demonstrating a < PMER and ≥ PMER for technical response was 83% and 75% respectively. Conclusion: EBD for symptomatic Crohn's strictures shows high efficacy with a low complication rate. Efficacy may be affected by active inflammation and previous surgery. Variation exists in the quality of reporting of the studies. Further well designed comparative studies capturing differential effects of stricture types are needed. Disclosure of interest: None Declared.